Valorization of disposable Covid-19 personal protection equipment through the thermo-chemical process / Ahmed Faizal Ayub Khan - Ahmed Faizal , Ayub Khan (2022)
Medical waste in the form of Personal Protective Equipment (PPE) has been in the rise in these days especially due to the pandemic hit in 2019. These surge in medical wastes skyrocketed as compared to previous years making it one of the wastes that had to divert our attention to treat it properly. Several attempts at treating it has been done such as incineration, landfill, chemical disinfection microwave and autoclaving but pyrolysis had been found out to be one of the viable options that is much greener than the others. Through pyrolysis a usable and beneficial product can be obtained in the form of hydrocarbon while ensuring the environment clean. The hydrocarbon which is the bio-oil obtained from the pyrolysis process had to be of good quality in order it to be compatible for substitution of petroleum-based oil. As such upgradation of the oil is also essential due to the volatile nature of the PPE. This is where the coconut shell/copra comes into play. Coconut shell can be also found abundant in Malaysia due high usage of coconut milk in households. With this opportunity, a co-pyrolysis process had been developed between PPE and CCS in this study. The experiment showed addition of coconut shell (CCS) to PPE for co-pyrolysis had decreased the yield of the bio-oil when compared to pure pyrolysis of PPE and CCS. This is due to the CCS being already a good feedstock itself by having high amount of hydrocarbon compound produced. The yield drop can be also explained due to the volatile nature of PPE and most of the compounds formed in gaseous state. However, from the HHV analysis, it has also been found there was significant increase in hydrocarbon compounds in co-pyrolysis product when compared to pure PPE. The amount of esters and other oxygenates also been removed from CCS due to synergistic effect making the final product of co-pyrolysis that has much better heating value at 20% when compared to PPE and 50% to CCS with much closer attribute to the petroleum-based hydrocarbon. This study concludes that by having CCS introduced to PPE, the bio-oil yield had dropped but the quality of the bio-oil obtained of better quality.